RAPID GROWTH OF CHARGED-PARTICLE MULTIPLICITY IN HIGH-ENERGY E+E- ANNIHILATIONS - Brandelik, R; Braunschweig, W; Gather, K; Kadansky, V; Lubelsmeyer, K; Mattig, P; Martyn, H; Peise, G; Rimkus, J; Sander, H; Schmitz, D; Schultzvondratzig, A; et al. (1980)
Hadron production by e+e- annihilation has been studied for c.m. energies W between 13 and 31.6 GeV. As a function of 1n W the charged particle multiplicity grows faster at high energy than at lower energies. This is correlated with a rise in the plateau of the rapidity distribution. The cross section sdσ/dx is found to scale within ±30% for x > 0.2 and 5 ≤ W ≤ 31.6 GeV. © 1980.